PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN UNTUK PENILAIAN PRESTASI BELAJAR SISWA SEKOLAH DASAR PUSAKA BANGSA - Winnie Septiani; Ivanna Ivanna (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
School of Pusaka Bangsa was founded by Yayasan Pusaka Bangsa and started operating from academic year 1999/2000. This school still uses an assessment system that focuses on the academic aspect of the students. The decision-supporting system suggested is a system that allows the holistic evaluation of the studesnts achievement that includes academic achievement, behaviour, extra curricular activities and attendance. The designing of the system consists of planning steps, research, analysis, design, construction and implementation. The decision-supporting system in the School of Pusaka Bangsa Karawang has a few functions. The first one is as a data keep, where we can use it to add, change and delete the data of students and teachers. The second function is the assessments of the students that is used to give a final score of the students achievements according to the attributes in the assessments that varied for each academic levels.. The third function of the system is students analysis diagram which gives the diagram of the students score. The applications of the decision-supporting system gives a better result. This improvement can be observed from the ratio of the work evaluation before development and those after are 2.58 and 4.18 respectively. The indicator of the evaluations are completeness, ease, timing, accessibility and information representations.